2010
DOI: 10.1007/s11103-010-9676-6
|View full text |Cite
|
Sign up to set email alerts
|

A plant secretory signal peptide targets plastome-encoded recombinant proteins to the thylakoid membrane

Abstract: Plastids are considered promising bioreactors for the production of recombinant proteins, but the knowledge of the mechanisms regulating foreign protein folding, targeting, and accumulation in these organelles is still incomplete. Here we demonstrate that a plant secretory signal peptide is able to target a plastome-encoded recombinant protein to the thylakoid membrane. The fusion protein zeolin with its native signal peptide expressed by tobacco (Nicotiana tabacum) transplastomic plants was directed into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Plastid-encoded pre-Tic40 was properly processed and targeted and assembled into a functional complex at the inner membrane of chloroplast (Singh et al 2008). Zeolin with a plant secretory signal peptide was targeted to the thylakoid membrane upon chloroplast transformation (De Marchis et al 2011). Recombinant disulfide-bond containing proteins can be expressed in transformed plastids when targeted to the lumen of thylakoids (Bally et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Plastid-encoded pre-Tic40 was properly processed and targeted and assembled into a functional complex at the inner membrane of chloroplast (Singh et al 2008). Zeolin with a plant secretory signal peptide was targeted to the thylakoid membrane upon chloroplast transformation (De Marchis et al 2011). Recombinant disulfide-bond containing proteins can be expressed in transformed plastids when targeted to the lumen of thylakoids (Bally et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that a ER plant signal peptide is capable of carrying a fusion protein called zeolin, whose gene is inserted into the plastoma, to the thylakoid membranes, where the recombinant protein accumulates as trimers. In the stroma, the folding of the same protein without the signal peptide is hampered as the protein accumulates at low amounts in a monomeric form (De Marchis et al, 2011). Thus, we can speculate that whatever is the sorting mechanism that directs zeolin to the thylakoids, it probably also has a stabilizing effect on the recombinant protein (Fig.…”
Section: Localization Of Recombinant Protein Containing Covalent Disumentioning
confidence: 98%
“…The accumulation of phaseolin in the ER was much higher than that in the vacuole, both as phaseolin-KDEL (data not shown) and as zeolin (arrowhead), which forms large aggregates (vertical bar) due to the formation of interchain disulfide bonds (Mainieri et al, 2004). In the chloroplast (CHL) of transplastomic plants expressing the phaseolin fusion protein zeolin, the recombinant protein devoid of its signal peptide (Dzeo) was barely detectable in the stroma (str; lanes 5 and 6); conversely, when targeted to the thylakoid membrane (thy; lanes 7 and 8), it is clearly detectable (De Marchis et al, 2011). Molecular mass in kD (numbers at right) is indicated.…”
Section: Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…23,28 Post-translational modifications, such as disulphide bond formations, can influence the stability of recombinant proteins produced in plastids contributing to protein accumulation. 28 Moreover, correct folding of the proteins by formation of disulphide bonds is often required for functional tertiary and quaternary structures and, therefore, for antigenicity of the recombinant proteins expressed in transplastomic plants. 3 On the other hand, glycosylation is absent in plastids, preventing the production of glycoproteins.…”
Section: Additional Challengesmentioning
confidence: 99%